2016
DOI: 10.1101/077586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptic vesicle glycoprotein 2C (SV2C) modulates dopamine release and is disrupted in Parkinson’s disease

Abstract: The synaptic vesicle glycoprotein 2 (SV2) family of proteins are involved in synaptic function throughout the brain. The ubiquitously expressed SV2A has been widely implicated in epilepsy, though SV2C with its restricted basal ganglia distribution has no known function. SV2C is emerging as a potentially relevant protein in Parkinson's disease, as it is a genetic modifier of nicotine neuroprotection and sensitivity to L-DOPA. Here we identify SV2C as a mediator of dopamine homeostasis and report that disrupted … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 62 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Synaptic dysfunction and altered axonal transport has been postulated to be some of the earliest pathological events in PD, in which α-Syn is considered a hub protein by interacting with many synaptic proteins, such as monoamine transporters, cytoskeletal components, chaperones, and several SV-associated proteins [52,73,74]. In this regard, increases of the SV2C protein -enriched in the basal ganglia and preferentially localized in DA neurons-were reported in postmortem PD brain tissue and in mice overexpressing mutant α-Syn [59]. Similarly, we found increased levels of SV2A protein-expressed ubiquitously in the brain-and even co-localizing with h-α-Syn in axonal swellings through CPu and Cg of AAV5 mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic dysfunction and altered axonal transport has been postulated to be some of the earliest pathological events in PD, in which α-Syn is considered a hub protein by interacting with many synaptic proteins, such as monoamine transporters, cytoskeletal components, chaperones, and several SV-associated proteins [52,73,74]. In this regard, increases of the SV2C protein -enriched in the basal ganglia and preferentially localized in DA neurons-were reported in postmortem PD brain tissue and in mice overexpressing mutant α-Syn [59]. Similarly, we found increased levels of SV2A protein-expressed ubiquitously in the brain-and even co-localizing with h-α-Syn in axonal swellings through CPu and Cg of AAV5 mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the h-α-Syn accumulation in innervation networks can alter the density of synaptic proteins, such as the synaptic vesicle (SV)-associated proteins, which are ubiquitously expressed in the brain and modulate vesicular function [59], we performed an exploratory analysis of the SV2A protein levels in Cg and CPu from mice overexpressing h-α-Syn in raphe 5-HT neurons. Immunofluorescence analysis showed a progressive increase in punctate SV2A staining in these regions compared to vehicletreated mice (p < 0.01; Fig.…”
Section: Characterization Of the Mouse Model With H-α-syn Overexpress...mentioning
confidence: 99%
“…Although we have not identified a direct proteinprotein interaction between VMAT2 and SV2C, these proteins appear to work in concert to modulate dopamine dynamics (Dunn et al, 2017). A study that performed transcriptomics in mice with knock-out of VMAT2 in norepinephrine neurons identified SV2C as the gene with the highest enrichment in expression following VMAT2 knock-out in multiple brain areas (Isingrini et al, 2023).…”
Section: Introductionmentioning
confidence: 68%
“…A study that performed transcriptomics in mice with knock-out of VMAT2 in norepinephrine neurons identified SV2C as the gene with the highest enrichment in expression following VMAT2 knock-out in multiple brain areas (Isingrini et al, 2023). We have additionally shown that animals lacking SV2C have decreased dopamine content in the striatum, as well as impaired evoked dopamine release (Dunn et al, 2017). These animals also displayed decreased locomotor activity correlating with the decrease in dopamine transmission (Dunn et al, 2017).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation